Supporting Collaboration between Customers and Developers: A Framework for Distributed, Agile Software Development - Bergadano, Francesco; Bosio, Gianni; Spagnolo, Stefano (International journal of distributed systems and technologies, 2014)
The traditional, in-house software development process is progressively losing its appeal in favor of distributed, multi-site development: this is mainly due to the well-known advantages of the latter, such as higher productivity and lower costs. However, this practice has also some documented disadvantages that are inherent to distance: geographical, temporal and socio-cultural distances between stakeholders can affect communication, coordination and control activities, thus making collaboration very difficult. This would not immediately look as the ideal scenario for applying Agile methodologies, which definitely rely on continuous collaboration between all stakeholders, including (with a very important role) the customers. This paper analyzes issues related to collaboration between customers and developers in a distributed, Agile setting and proposes a framework that defines practices and tools for handling project information and communication activities.